2003
DOI: 10.1007/s00415-003-1105-z
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunctions in idiopathic Parkinson's disease

Abstract: Most patients with Parkinson's disease experience autonomic dysfunction at some point in the course of their disease. In contrast to autonomic dysregulation in multisystem atrophy, they are less severe, and they frequently cause troublesome symptoms only in advanced stages of the disease. The quality of life is nevertheless substantially restricted. Cardiovascular, gastrointestinal and urogenital autonomic dysfunction is predominant. Appropriate diagnosis and treatment can greatly benefit the patient. An inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 11 publications
2
62
1
13
Order By: Relevance
“…The estimated prevalence of autonomic dysfunction in PD ranges between 14% and 80%. 754 A recent study of 123 patients with PD and 96 agematched controls using a newly validated nonmotor questionnaire for PD (NMSQuest) reported that autonomic symptoms were significantly more common in all stages of the disease than in controls. 343 Another study evaluated autonomic symptoms in patients with PD using the SCOPA-AUT, and found that autonomic symptoms were more common in patients with PD than controls and increased in association with increasing age, disease severity, and medication use.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated prevalence of autonomic dysfunction in PD ranges between 14% and 80%. 754 A recent study of 123 patients with PD and 96 agematched controls using a newly validated nonmotor questionnaire for PD (NMSQuest) reported that autonomic symptoms were significantly more common in all stages of the disease than in controls. 343 Another study evaluated autonomic symptoms in patients with PD using the SCOPA-AUT, and found that autonomic symptoms were more common in patients with PD than controls and increased in association with increasing age, disease severity, and medication use.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
“…Autonomic dysfunction, including constipation, nocturia, and orthostatic hypotension, can be disabling for some patients with PD and have a significant effect on their quality of life. 754 Autonomic dysfunction in PD is attributed to pathologic involvement of central and peripheral autonomic neurons. The ventrolateral medulla, nucleus tractus solitarius, periaqueductal gray matter in the midbrain, descending sympathetic and parasympathetic pathways, and peripheral autonomic neurons and ganglia have all been reported to have Lewy bodies and to be involved in the PD neurodegenerative process.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
“…For example, disturbances of gastrointestinal function observed in those patients, such as constipation and delayed gastric emptying, detract immensely from www.fhc.viamedica.pl quality of life, even though do not pose an imminent life-threatening situation. Epidemiological evidence has shown that gut dysfunctions even predate well-defined motor symptoms [4][5][6][7]. Braak et al proposed that the pathological staging of the disease should be directly linked to its clinical progression.…”
Section: Introductionmentioning
confidence: 99%
“…Распространенность вегетативных нарушений у пациентов с БП варьирует от 14 до 80% в зависимо-сти от стадии заболевания [89]. При ортостатиче-ской и постпрандиальной гипотензии помимо наи-более частых жалоб на рассеянность внимания, не-четкость зрения, головокружение, обмороки и пред-обморочные состояния пациенты также могут предъявлять жалобы на ДС [90].…”
Section: дс как маска ортостатической и постпрандиальной гипотензииunclassified